46. SITUATION OF SELF-CAREING AND SOME FACTORS RELATED TO COMPLAINTIONS OF PATIENTS WITH CKD AT AN GIANG CENTRAL HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the self-care ability and identify factors associated with complications in patients with chronic kidney failure at An Giang Central General Hospital in 2023.Subjects and Methods: A cross-sectional descriptive study with analysis was conducted on 196 patients treated at the Department of Nephrology - Internal Medicine, An Giang Central General Hospital. Data were collected using a pre-designed questionnaire through face-to-face interviews.Results: Complications were observed in 82.1% of chronic kidney failure patients, with cardiovascular disease being the most common comorbidity 50%. Low self-care scores were reported in 89.8% of patients, and 86.2% lacked knowledge about the disease. Significant associations were found between complications and age, education level, self-care ability, and knowledge (p < 0.05).Conclusions: The majority of patients 89.8% had low self-care scores, and both self-care ability and knowledge were associated with complications. Routine assessment of self-care ability upon admission and interventions to slow the progression of chronic kidney failure are recommended.
Keywords: Chronic kidney failure, CKD complications